A Framework for Game-based Soft Skills Development: A Case of Inventors of Future - Bee Sian, Tan; Wee Hoe, Tan; Wee Hing, Cho; Zamzuri Mohamad Ali, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Sophisticated human-machine interfaces can be configured through game-based training programs in the fourth industrial revolution (IR4.0), but their potential cannot be exploited without a proper framework that connects games to skills development. This paper proposed a game-based framework that focuses on critical thinking, problem-solving, and creativity for educators who intend to develop soft skills through games. Materials and Method: To develop this framework, a series of semi-structured interviews were conducted with game technologists, grassroots innovators, and practitioners of inventive problem-solving. A digital game was developed based on this framework. Results: A mobile game prototype named "Inventors of Future" was created as an instance of the framework, featuring three missions that allow learners to learn, invent, and assess ideas and solutions for inventive problem-solving. These game features are constructively aligned to critical thinking, problem-solving, and creativity skills, which are parallel to IR4.0. Conclusion: This paper discusses the development of a game-based framework for learning soft skills. This framework aims to equip learners with soft skills by playing a bespoke digital game. The framework is grounded on three learning facets: (a) contents of soft skills selected for deploying strategies in learning activities; (b) technology for creating invention games, which maps structural game elements against intended learning outcomes; and (c) assessment rubrics, which measure the attainment of learning outcomes. Upon the completion of these missions, learners should be able to visualize their inventions using a virtual pen and canvas in the game.